Description of the natural history and immature stages of Postplatyptilia caribica Gielis in Puerto Rico (Lepidoptera: Pterophoridae) - Matthews, Deborah L.; Pérez, Mervin E. (Zootaxa, 2014)
Observations of the life history of a plume moth, Postplatyptilia caribica Gielis are presented along with an adult diagnosis and descriptions of the final instar larva and pupa. The species was previously known only from two female specimens. Illustrations are provided for the adults and immatures, including both male and female genitalia. Morphological characters of the adults and immatures are discussed and compared with other members of the tribe Platyptiliini. Identification of adults and immatures is especially important because one of the larval hostplants, Gesneria pauciflora Urb., is a threatened endemic species of Puerto Rico. The plant family Gesneriaceae is a new addition to the known plant families used by Pterophoridae.